2016
DOI: 10.1017/dmp.2015.179
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Trust and Ability of Elderly Victims to Perform Activities of Daily Living in the Ya’an Earthquake Reconstruction Area, China

Abstract: A high level of interpersonal trust can significantly improve the ADLs of elderly persons. However, this may be achieved by weakening the negative effect of deteriorating social structure of victims. Attention should be focused on elderly victims whose social network worsens to improve their ADLs. (Disaster Med Public Health Preparedness. 2016;page 1 of 7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The findings are consistent with the number of post-earthquake studies in which the functional status of older survivors was associated with older adults' HQL. 34 The current study was consistent with a cross-sectional study on predictors of quality of life and depression among 189 older people living in temporary houses at 13 months after the Wenchuan earthquake in western China that reported IADLs as predictors of HQL. 35 Those older adults, who were physically, mentally, and socially active in the aftermath of the earthquake, had better HQL.…”
Section: Functional Statussupporting
confidence: 89%
“…The findings are consistent with the number of post-earthquake studies in which the functional status of older survivors was associated with older adults' HQL. 34 The current study was consistent with a cross-sectional study on predictors of quality of life and depression among 189 older people living in temporary houses at 13 months after the Wenchuan earthquake in western China that reported IADLs as predictors of HQL. 35 Those older adults, who were physically, mentally, and socially active in the aftermath of the earthquake, had better HQL.…”
Section: Functional Statussupporting
confidence: 89%
“…There are two classical schools of thought who viewed social trust differently; the social psychological thought believes in individualism, while the societal school of thought believes in collectivism. According to social-psychological school of thought, trust is an essential element of an individual's personality traits (Liang & Ju, 2016), because an individual's learning about trust starts from his or her home, and this childhood socialization changes with the passage of time as the experience is gained (Uslaner, 2000). Moreover, social trust is reliant not only on the reciprocity of experience, but is also closely associated with the subjective feelings and the kind of the personality that an individual has (Uslaner, 1999).…”
Section: The Moderating Role Of Social Trustmentioning
confidence: 99%
“…The relationship between widowhood and ADL scores has received some attention (Hacihasanoğlu et al, 2012; Poppel & Joung, 2001). Previous research has shown that widowed individuals are more likely to develop an ADL‐related disability (Hsiao et al, 2021) and are more vulnerable to deterioration as a result of an ADL‐related disability (Liang & Ju, 2016; Qian et al, 2016; Zhang et al, 2019). Aside from ADL scores, hospitalisation is also a critical predictor of objective health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that widowed individuals are more likely to develop an ADL-related disability (Hsiao et al, 2021) and are more vulnerable to deterioration as a result of an ADL-related disability (Liang & Ju, 2016;Qian et al, 2016;Zhang et al, 2019).…”
mentioning
confidence: 99%